Morbidity and Mortality Outcomes of Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy at a Single Institution in Japan - Akiyoshi Mizumoto; Emel Canbay; Masamitsu Hirano; Nobuyuki Takao; Takayuki Matsuda; Masumi Ichinose; Yutaka Yonemura (Gastroenterology Research and Practice)
Background. Even though cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are associated with a high morbidity and mortality rates, it has been reported that CRS and HIPEC improved survival of selected patients with peritoneal carcinomatosis. We aimed to report morbidity and mortality results of CRS and HIPEC from a single institution in Japan. Methods and Results. Total of 284 procedures of CRS were performed on patients with pseudomyxoma peritonei, peritoneal carcinomatosis (PC) from colon cancer and gastric cancer between 2007 and 2011 in our institution. The morbidity rate was 49% of all procedure, and grades I/II and grades III/IV complications were 28% and 17%, respectively. Most frequent complication was surgical site infections including intraabdominal abscess. The mortality rate was 3.5%, and reoperation was needed in 11% of all procedures. Univariate and multivariate analysis showed peritoneal carcinomatosis index (PCI) greater than 20 was the only significant factor for occurrence of postoperative complications (P<0.01). In contrast, HIPEC significantly reduced postoperative complications (P<0.05). Conclusions. The morbidity and mortality rates of our institution are comparable with previous reports that are in acceptable rates. Optimal patient selection such as patients with PCI less than 20 seems to be of paramount importance to CRS and HIPEC.